2018
DOI: 10.4102/curationis.v41i1.1924
|View full text |Cite
|
Sign up to set email alerts
|

The effects of absenteeism on nurses remaining on duty at a tertiary hospital of Limpopo province

Abstract: BackgroundAbsenteeism is a global problem in the working force and this is no exception in the nursing profession. Much attention has been drawn to factors that contribute to absenteeism; however, little attention has been placed on the effects of absenteeism on nurses remaining on duty by their colleagues. Nurses absent themselves leaving behind their colleagues to execute their part of work.ObjectivesTo investigate the effects of absenteeism on nurses who remained on duty at a tertiary hospital in Limpopo pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
2
16
0
3
Order By: Relevance
“…Strengths of this study include use of the criterion standard burnout assessment instrument (the Maslach Burnout Inventory) and statistical adjustment for symptoms of depression and fatigue. Future research should explore additional factors likely to impact absenteeism and work performance, leverage employer data on absences and job performance, use longitudinal study designs, and further explore the effects of absenteeism on the colleagues impacted by the nurses who are absent [65].…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this study include use of the criterion standard burnout assessment instrument (the Maslach Burnout Inventory) and statistical adjustment for symptoms of depression and fatigue. Future research should explore additional factors likely to impact absenteeism and work performance, leverage employer data on absences and job performance, use longitudinal study designs, and further explore the effects of absenteeism on the colleagues impacted by the nurses who are absent [65].…”
Section: Discussionmentioning
confidence: 99%
“…Since it affects the psychological and professional well-being of nurses, consequences such as provision of substandard patient care, increased risk of medical errors and a potentially unhealthy environment are expected for nurses who remain on duty (Mbombi, Mothiba, Malema, & Malatji, 2018). Therefore, thinking about the health of outpatient clinic nursing professionals requires reflecting on existing microprocesses in care units and their implications for workers.…”
Section: Abs Enteeis Mmentioning
confidence: 99%
“…A qualitative study found that in addition to the inadequate staffing and workload, absenteeism added pressure during work hours that led to job dissatisfaction [ 24 ]. A study among 186 nurses in Limpopo, South Africa also found that absenteeism affected the nurses who remained on duty while their colleagues were absent in the aspect of low morale, psychological stress, and increased workload, consequently jeopardizing patient care with the risk of medical errors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%